Pengaruh Jenis Biochar dan Jarak Tanam Terhadap Pertumbuhan dan Hasil Padi Gogo (Oryza sativa L.): Effect of Biochar Types and Plant Spacing on The Growth and Yield of Upland Rice (Oryza sativa L.) - Ai Fitria; Nasrudin Nasrudin; Siti Nurhidayah (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
Upland rice has the potential to be cultivated on land that has limited water. Plant spacing needs to be done as a strategy so that upland rice can absorb light and water optimally. Apart from that, biochar can be used to improve soil properties so that it is suitable for supporting the growth of upland rice plants on dry land. The study aims to examine the response of biochar application and plant spacing on the growth and yield of upland rice. The study was conducted in the experimental garden of the Faculty of Agriculture, Universitas Perjuangan Tasikmalaya at an altitude of 359 meters above sea level. This study used a factorial Randomized Completely Block Design (RCBD). The first factor is a type of biochar consisting of coconut shells and rice husks charcoal. The second factor is the plant spacing consisting of 20 x 20 cm and 30 x 30 cm. The results showed that there was no interaction between the two treatments on the growth and yield of upland rice. The application of biochar had a significant effect on the number of panicles per hill, while plant spacing had a significant effect on the root length, root wet weight, 1.000 seed weight, and yield. The coconut shell was able to increase the number of panicles per hill, while the wider plant spacing caused an increase in root length, root wet weight, 1.000 seed weight, and yield. In general, the application of biochar can improve crop yields, while regulating the plant spacing has the potential to increase the growth and yield of upland rice.